Perception of Obstructive Sleep Apnea Among Civil Servants in Enugu State - Okoli, Ogechukwu N.; Obi, Evelyn Chinwe; Chiaghana, Chiazor; Ono, Gloria Nneka (Social Science Research, 2024)
Obstructive sleep apnea is a markedly prevalent condition across the lifespan of particularly adult patients and overweight individuals, one of the most frequent symptoms leading to clinical referral for evaluation and treatment is abnormal breathing during sleep in which breathing repeatedly stops and starts. This paper examined the perception of obstructive sleep apnea among civil servants in Enugu state. The objectives of this study are to find out the awareness level, perception, and response of Civil Servants in Enugu State about Obstructive sleep apnea. The health belief Model was employed to explain certain health behaviors of some individuals. The survey method was done using a questionnaire as a data collection instrument. A sample of 371 respondents was drawn from the population of the study which comprises Civil Servants in Enugu State. Findings from the study showed that the majority of civil servants are not aware of this health condition. Lastly, since they are unaware of the symptoms and risk factors associated with sleep apnea, they are not ready to go for a proper diagnosis because they do not believe that they may be suffering from sleep apnea. The study recommended, that there should be massive and aggressive health communication campaigns for the awareness and knowledge of sleep apnea, its signs, and symptoms; medical personnel through their faceto-face communication with patients should help correct some of the misconceptions about the health condition and stress the dangers of poor diagnosis.